Research Productivity of Teacher Educators - Suryakala, Dr. R. (Voices of Teachers and Teacher Educators, 2021)
Research is an effort to bridge theory with practice. It also helps in refining the existing practices. Research must be an integral part of the Teacher Educators’ work as educational research has a trickle-down effect that leads to quality at all levels of education. This article documents the research productivity of Teacher Educators and the factors affecting their research productivity. The findings reveal the research productivity of a sample of teachers in Thoothukudi district, Tamil Nadu tabulated on a scale prepared for measuring engagement with research The findings also throw light on the factors that impact the research productivity of Teacher Educators